Stress corrosion cracking in fuel-grade anhydrous ethanol from dedicated and multi-products pipelines. (July 2021) - dos Santos, C.A.L.; de Almeida, N.L.; Panossian, Z.; Tiroel, L.C.O.; Jorge, V.A.; Oliveira, E.C.
Highlights: Standard SSRT and notched specimens were used to study SCC in fuel-grade ethanol. SCC was observed to anhydrous ethanol fuel from multi-products pipeline. Quasi-cleavage cracks occurred in anhydrous ethanol fuel from dedicated pipeline. These cracks have not seen before in literature. Brazilian fuel sugar cane ethanol matrix is receiving fuel corn ethanol lately. Abstract: In this study, anhydrous ethanol fuel samples obtained from pipelines dedicated to the ethanol fuel transport and from multi-product pipelines were tested by standard slow strain stress tests and API 5L X65 notched specimens. The fractures of the specimens were observed by optical and scanning electron microscopes. The metallographic examination of a normal section of the fracture surface was carried out. It was observed that the ethanol samples from multi-product pipelines were more aggressive than the ethanol fuel from dedicated pipeline samples. On the other hand, ethanol fuel from dedicated pipeline samples presented quasi-cleavage fractures which have not been seen before in the literature. Nowadays, it has been known that Brazilian Midwest is producing fuel ethanol from second crop corn. This study sheds light on a possible change in the Brazilian fuel ethanol matrix that in the past was predominantly composed of sugar cane ethanol and is currently receiving the contribution of corn ethanol in order to avoid any transport and storage system failure.